Budaya Organisasi Memoderasi Pengaruh Komunikasi Internal dan Kepemimpinan Transformasional terhadap Employee Engagement - Dimençia Canossa Da Costa Amaral; Miswanto Miswanto; Frasto Biyanto; Anacleto Roberto Carolina Soares; Baldric Siregar (Lembaga Penelitian Dan Publikasi Ilmiah (lppi) Yayasan Almahmudi Bin Dahlan, 2026)
Employee engagement is an important factor in improving performance and effectiveness within public sector organizations. However, employees’ level of engagement is often influenced by the quality of internal communication, leadership practices, and organizational culture. This study examines the effects of internal communication service quality and transformational leadership on employee engagement, with organizational culture serving as a moderating variable among civil servants in Timor Leste. A quantitative survey approach was employed involving 250 respondents selected through proportional random sampling. Data were collected using questionnaires and analyzed using Partial Least Squares Structural Equation Modeling. The findings indicate that internal communication service quality and transformational leadership have positive effects on employee engagement. Organizational culture was also found to strengthen the relationship between these variables and employee engagement. The study highlights the importance of effective communication, transformational leadership, and a supportive organizational culture in fostering higher employee engagement in public sector institutions.